Pernikahan Beda Agama Perspektif Ulama Tafsir Lintas Mazhab - Solehodin; Khairun (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
The Qur'an has clearly regulated interfaith marriage, which prohibits Muslims from marrying non-Muslims. However, Muslim society often opposes this by marrying people of different beliefs. This article discusses religious marriage according to inter-school interpretation scholars. Referring to the primary source of the book Ahkam al-Quran by Abu Bakr Ahmad bin Ê¿Ali al-Razi al-Jaá¹£á¹£Äá¹£, Ahkam al-Quran by Abu Bakr bin Abdullah bin al-Arabi, Ahkam al-Quran by 'Imad al-Din bin Muhammad al-Tabari al Kiya al-Harasi and Zadu al-Masir fi 'Ilm al-Tafsir by Abu al-Faraj Jamal al-Din bin Abd al-Rahman al-Jawzi. This article uses a descriptive qualitative method. Scholars of interpretation across schools of thought agree that it is forbidden to marry infidels and polytheists. The difference of opinion lies in the marriage to the people of a ahli kitab. There are scholars who absolutely do not allow marrying people of a ahli kitab, because people of a ahli kitab are someone who associates partners with Allah. The second opinion is that it is permissible to marry people of a ahli kitab on condition that they have converted to Islam. Third, it is permissible to marry people of a ahli kitab, provided that the intention of people of a ahli kitab are Jews and Christians. Fourth, it is makruh to marry people of a ahli kitab.